(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
This research aimed to Compare the biochemical composition (protein, lipid) for Caranx crysos and Sargocentron rubrum with average weight 68±0.1g. The fish were collected from the area facing the estuary of Marqia River-Al-Kharab-Tartous city beach, during autumn of 2021.. The results showed that C. crysos gives protein level 18.92% higher than S. rubrum 16.82%. On the contrary, the lipid level in S. rubrum was 11.63% higher than in C. crysos 2.3%. Sargocentron rubrum is high fat content, and Caranx crysos is low fat content according to (Ackman, 1989) .